Contribution of Medical Wards Contamination to Wound Infection among Patients Attending Ruhengeri Referral Hospital - Emmanuel Munyeshyaka; Parfait Cyuzuzo; Callixte Yadufashije; John Karemera (International Journal of Microbiology)
Nosocomial infections or hospital-acquired infections are infections that potentially occur in the patients under medical care. These infections are often caused by multidrug-resistant pathogens acquired via improper antibiotic use, not following infection control and prevention procedures. The main objective of this study was to investigate the contribution of medical wards contamination to wound infection and antibiotics susceptibility patterns at Ruhengeri Referral Hospital, Musanze district, Rwanda. This was a cross-sectional study where a total of 61 samples including air sampling to evaluate the contamination by airborne bacteria, working surface, equipment, and patients’ surgical wounds swabs were collected in intensive care unit (ICU), pediatrics, and surgery departments. Culture, Gram stain, and biochemical tests were performed for microbiological isolation and identification. Antibiotic susceptibility testing was performed using the Kirby–Bauer disc diffusion method. Statistical Package for Social Science (SPSS) version 22 was used for data analysis. Gram-negative bacteria were frequently from surgery, pediatric, and ICU with 68.8%, 63.9%, and 31.1%, respectively, while Gram-positive isolates were 37.7% in surgery, 32.9% in pediatric, and 18.0% in ICU. There was a statistically significant association with E. coli and swabbed materials and surgical wound sites (x2 = 10.0253, P value = 0.018). All bacterial contaminants were sensitive to clindamycin and erythromycin. Pseudomonas aeruginosa, E. coli, and S. aureus were resistant to nitrofurantoin. Hospital environment could be a contributing factor to surgical wound site infections. Hospitals should apply preventive measures in the hospital environment surrounding wound surgery patients to prevent wound infections during hospital stay.